2019
DOI: 10.18517/ijaseit.9.4.7218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bismuth Oxide Nanoparticles as Radiosensitizer for Megavoltage Radiotherapy

Abstract: Metal-based nanoparticles such as gold, silver, platinum, and bismuth have been widely investigated for radiotherapeutic application. Basic understanding of the cellular interaction of the nanoparticles with the biological materials is crucial to ensure future clinical use. In this study, the cytotoxicity, cellular uptake, and generation of reactive oxygen species (ROS) induced by BiONPs were investigated prior elucidating the feasibility of BiONPs for radiotherapy application using megavoltage photon and elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
(85 reference statements)
0
17
0
Order By: Relevance
“…The BiONPs have been observed surrounding the nuclei or scattered in the cytoplasm, which proves BiONPs penetration into the cells. In our recently published work, the BiONPs uptake into the cells was demonstrated quantitatively using flow cytometry gating, in which the high Q2 quadrant percentage for treatment of BiONPs onto the cells indicated the cellular uptakes of BiONPs 25. Theoretically, the BiONPs could enter the cells through macropinocytosis pathway, which is a cell transport system with a minimum of 0.5 µm vesicular size 26.…”
Section: Discussionmentioning
confidence: 98%
“…The BiONPs have been observed surrounding the nuclei or scattered in the cytoplasm, which proves BiONPs penetration into the cells. In our recently published work, the BiONPs uptake into the cells was demonstrated quantitatively using flow cytometry gating, in which the high Q2 quadrant percentage for treatment of BiONPs onto the cells indicated the cellular uptakes of BiONPs 25. Theoretically, the BiONPs could enter the cells through macropinocytosis pathway, which is a cell transport system with a minimum of 0.5 µm vesicular size 26.…”
Section: Discussionmentioning
confidence: 98%
“…In a previous study, we have conducted in vitro cytotoxic effect which concluded the 0.5 mM as the biocompatible concentration used in this study. 13 Cisplatin (Cis) (Tokyo Chemical Industry) was prepared as 41.7 µM in dimethyl sulfoxide (DMSO) (Fisher Scientific) solvent and stored at −20°C. Cis was treated onto the cells to a final concentration of 1.30 µM within the well, based on the cytotoxicity assay in our recently published work.…”
Section: Bionps Cis and Brf Preparationsmentioning
confidence: 99%
“…The model is represented by the linear component [exp (-αD)], which is designated for a single hit to the double-strand of DNA breakage and a quadratic component [exp (-βD2)] which denoted the double hits that induce double-strand damage of the chromosomes. 12,13 The sensitization enhancement ratio (SER) was extrapolated from the LQ graph fittings. The values indicated the radiosensitization effect by each treatment component and were calculated using the formula as in Equation 4.…”
Section: Sf =mentioning
confidence: 99%
See 2 more Smart Citations